Characterisation of an optimised high current MgO/Bi2Sr2CaCu2O8.21 composite conductor using pulsed transport currents with pulsed magnetic fields - Glowacki, B; Gilewski, A; Rogacki, K; Kursumovic, A; Evetts, J; Jones, H; Henson, R; Tsukamoto, O (2003)
High temperature superconducting conductors are already used in hybrid magnets to produce fields that enhance the performance of conventional magnets made from A-15 type low temperature superconducting wires. For such applications it is vital that the interdependence of the critical parameters such as critical current versus magnetic field can be mapped under high field and high current conditions. However these superconductors have high critical currents even at fields over 20 T, making accurate measurements difficult due to the thermal and mechanical problems. In this paper, we compare measurements on the fully optimised Bi2Sr2CaCu2O8.21 flat rigid conductors using an innovative pulsed high transport current and pulsed high field technique. We show how analysis of the voltage signal from Bi2Sr2CaCu2O8.21 tape in pulsed conditions may be used to extract the critical current under quasi-stationary conditions. © 2002 Elsevier Science B.V. All rights reserved.